Pentingnya Motivasi Mahasiswa dalam Ketepatan Menyelesaikan Tugas Akhir di Akademi Keperawatan Columbia Asia Medan - Rispalina Ritonga; Romauli Siallagan (Yayasan Literasi Sains Indonesia, 2022)
Motivation is an encouragement that comes from internal or external which causes a person to do an action with the aim of achieving the goals to be achieved. High motivation is needed for students to complete their final assignment in their studies, namely scientific writing. This study aims to determine the relationship between motivation in completing the final task. This research is a correlative descriptive study using a cross sectional approach. This research was conducted on the Columbia Asia Nursing Academy campus area in Medan. Sampling in this study used total sampling by means of observation using demographic data and motivational questionnaires. The level of student motivation in completing the final assignment is very influential for the students themselves in the preparation and completion of the final assignment.